PENGARUH VARIETAS DAN SISTEM PERSIAPAN LAHAN PADA TANAMAN JAGUNG - Ridwan Ridwan; Yulinar Zubaidah (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2005)
Maize productivity was affected by land preparation system, crop variety, and management. A field experiment was conducted in Guguk Lima Puluh Kota Regency during planting season 2002 (from July to November 2002). The experiment was designed in a split plot design with three replications. Two varieties of corn (Bisma and P10-hybrid) as a main plot and three methods of land preparation (no tillage, conventional tillage, and strip tillage) as a subplot. Objectives of the experiment were to find out a combination of better crop variety and land preparation methods on maize growth. The results of the experiment showed that maize P 10-hybrid gave the shorter plant height, the higher number of seeds /cob and yield. Bisma and P10-hybrid varieties gave yield 7.91 and 8.51 t/ha, respectively. Plant growth, yield components, and yield of maize had not been affected by land preparation methods. However, no tillage and strip tillage methods seemed to give higher yield (8.26 and 8.90 t/ha, respectively) and more efficient than conventional tillage. Key Words: maize variety, no tillage, conventional tillage, and strip tillage